MENGEFEKTIFKAN FUNGSI PENDIDIKAN KEWIRAUSAHAAN UNTUK MENGATASI PERSOALAN MUTU PERGURUAN TINGGI - H. sabil handaling (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2008)
To increase quality of output of college, hence entrepreneurship education especially at curriculum aspect, student, dosen, process study, and the aspect participate society represent strategic aspect. The components represent element in system of national education, but during the time not yet functioned better so that expectation of the increasing of education quality not yet also be reached.